Comparisons of High Intensity Interval Training and Continuous Training on Metabolomic Alteration and Cardiac Function in Male Adolescent Rats - Zheng, Molin; Liu, Chuanan; Lv, Yuanyuan; Mi, Jing; Qiu, Dan; He, Lingxiao; Zhao, Li (Frontiers in Physiology, 2022)
Background: Comparisons between high intensity interval training (HIIT) and continuous training (CT) regarding improvements of adolescents’ cardiac function are scarce and the preferred intensity for cardiac improvement with restricted myocardial damage remains unknown. This study conducted a 4-week training in male adolescent rats under moderate (MI) or high intensity (HI) HIIT and CT programs, aiming to discover and compare exercise-induced myocardial adaptations towards these two training methods. Methods: 39 male adolescent Sprague-Dawley rats (aged 4 weeks) were randomly assigned to high intensity HIIT (HI-HIIT, n=8), moderate intensity HIIT (MI-HIIT, n=8), high intensity CT (HI-CT, n=8), moderate intensity CT (MI-CT, n=8) and sedentary control (SC, n=7) groups. Rats in training groups were trained for 4 weeks and echocardiography was performed at baseline and after the final training. Serum creatine kinase myocardial band (CK-MB), cardiac troponin T (cTn-T) and untargeted metabolomics analysis were measured from blood samples collected 24 hours after the final training. Results: HIIT groups had greater cardiac output improvement than CT groups while no significant difference was found between the HI-HIIT and the MI-HIIT groups. HI-CT group showed higher serum CK-MB and cTn-T levels compared to MI-HIIT, MI-CT and control groups. Untargeted metabolomics analysis identified eleven HI-HIIT-related metabolites, five MI-HIIT-related metabolites and two HICT-related metabolites. The majority of the identified metabolites were phospholipid-related. Phosphatidylglyceride 18 level was significantly different between the HI-CT and MI-CT groups, and was negatively associated with cTn-T in CT groups. Conclusions: HIIT and CT improve cardiac function of adolescent rats while the HIIT demonstrates better improvement and less myocardial damage. High and moderate training intensities in HIIT exert similar cardiac benefits. HI-CT induced myocardial damage might be associated with serum phospholipids.